Photoelectrochemical properties of porphyrin dyes with a molecular dipole in the linker. (1st October 2015) - Ngo, Ken T.; Rochford, Jonathan; Fan, Hao; Batarseh, Alberto; Chitre, Keyur; Rangan, Sylvie; Bartynski, Robert A.; Galoppini, Elena
Abstract : The electronic properties of three porphyrin–bridge–anchor photosensitizers are reported with (1a, 1e, 3a and3e ) or without (2a and2e ) an intramolecular dipole in the bridge. The presence and orientation of the bridge dipole is hypothesized to influence the photovoltaic properties due to variations in the intrinsic dipole at the semiconductor–molecule interface. Electrochemical studies of the porphyrin–bridge–anchor dyes self-assembled on mesoporous nanoparticle ZrO2 films, show that the presence or direction of the bridge dipole does not have an observable effect on the electronic properties of the porphyrin ring. Subsequent photovoltaic measurements of nanostructured TiO2 semiconductor films in dye sensitized solar cells show a reduced photocurrent for photosensitizers1a and3a containing a bridge dipole. However, cooperative increased binding of the1a +3a co-sensitized device demonstrates that dye packing overrides any differences due to the presence of the small internal dipole.